1998
DOI: 10.1002/(sici)1097-0304(199803)43:3<298::aid-ccd12>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vessel wall morphology, blood flow velocity, and the hemostatic system in a patient with a large intracoronary thrombus

Abstract: A patient with AMI caused by a large thrombus in the proximal LAD was successfully treated with PTCA and an intracoronary lysis combined with the platelet‐receptor antagonist c7E3. Analysis of cellular hemostasis after 1 and 6 months revealed a sustained platelet activation despite combined anti‐platelet therapy with ASA and ticlopidine. A progredient slow‐flow phenomenon appeared during control angiographies, confirmed by intracoronary Doppler examination. Cathet. Cardiovasc. Diagn. 43:298–305, 1998. © 1998 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…20,21 It has also been reported that administration of the platelet GP IIb/IIIa receptor antagonist was effective for a patient with AMI caused by a large thrombus. 22 We therefore suggest that the treatment of the intracoronary thrombus, especially a large thrombus, is important during primary PTCA.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 It has also been reported that administration of the platelet GP IIb/IIIa receptor antagonist was effective for a patient with AMI caused by a large thrombus. 22 We therefore suggest that the treatment of the intracoronary thrombus, especially a large thrombus, is important during primary PTCA.…”
Section: Discussionmentioning
confidence: 99%
“…The intravascular ultrasound (IVUS) was not systematically implemented as it should be due to the retrospective nature of the current study. It was carried out in just 6 patients in the literature and shows an absence of atherosclerosis in two cases (44,45) in addition to inconspicuous signs of atherosclerosis in the other cases (46,47). Thus, prospective studies on the pathophysiological mechanisms using new technologies such as intravascular ultrasound (48) would allow better analysis of the vessel structure.…”
Section: Limitations Of the Studymentioning
confidence: 99%